On the State of Research into Coordination Compounds of Amino Acids with Metal Ions - Zayniddinovna, Tolusova Nasiba; Khudoyberdieva Malokhat Muminovna, (American Journal of Botany and Bioengineering, 2024)
Amino acids are essential substances for the life and activity of humans, animals and plants in nature, they are vital substances for all organisms, being part of proteins, peptides and tissues. Such an important feature of amino acids is due to their chemical composition and physicochemical properties. Among these properties, the amino acid molecule exhibits a neutral molecule, cationic and anionic states in one molecule depending on the environment (pH). In this case, the amino acid molecule polycondenses with its other molecules or with an unlimited number of other amino acid molecules, forming dipeptides, oligo- and polypeptides. This property is to have structures that arise as a result of the connection of peptides, due to their unique composition and the order of formation of proteins that perform various functions in the body.